A Contribution to the Optimization of the Reconfiguration Problem in Radial Distribution Systems - Macedo, Leonardo H. [UNESP] (2018)
Optimal reconfiguration is one of the most important strategies used to improve the operation of radially operated distribution systems. A large amount of research related to the reconfiguration problem has been carried out. Nevertheless, some topics still need to be discussed in order to provide guidance for future research related to the reconfiguration problem, such as the corresponding search space of the problem, optimization models that can be solved using exact optimization techniques, and the efficient implementation of metaheuristics. This paper addresses the following topics related to the reconfiguration problem: a detailed analysis of the search space of the problem and its relevance for developing efficient metaheuristics, an analysis of exact optimization models and their importance in the current context of optimizing the reconfiguration problem, and a detailed analysis of the main operators for the use of metaheuristics applied to the reconfiguration problem. Finally, the optimal solutions of the most analyzed systems in the literature are presented. Also, it is concluded that there is a need to set up a new database of larger and more complex systems to be used as a benchmark for new optimization proposals toward the solution of the reconfiguration problem.